Syringa oblata Lindl. Aqueous Extract Is a Potential Biofilm Inhibitor in S. suis - Bai, Jingwen; Yang, Yanbei; Wang, Shuai; Gao, Lingfei; Chen, Jianqing; Ren, Yongzhi; Ding, Wenya; Muhammad, Ishfaq; Li, Yanhua (Frontiers in Pharmacology, 2017)
Streptococcus suis (S. suis) is a zoonotic pathogen that causes severe disease symptoms in pigs and humans. Syringa oblata Lindl. distributed in the middle latitudes of Eurasia and North America were proved as the most development potential of Chinese Medicine. In this study, biofilm formation by S. suis decreased after growth with 1/2 MIC, 1/4 MIC, or 1/8 MIC of Syringa oblata Lindl. aqueous extract and rutin. Scanning electron microscopy analysis revealed the potential effect of Syringa oblata Lindl. aqueous extract and rutin against biofilm formation by S. suis. Using iTRAQ technology, we performed comparative proteomic analyses of cells at two different conditions: 1/2 MIC of Syringa oblata Lindl. aqueous extract treated and nontreated cells. The results revealed the existence of 28 proteins of varying amounts. We found that the majority of the proteins were related to cell growth and metabolism. We also found that Syringa oblata Lindl. Aqueous extract affected the CPS synthesis enzymes. In summary, Syringa oblata Lindl. aqueous extract might be used as a potential inhibitor for the control of biofilm formation by S. suis, and the active ingredients of the Syringa oblate Lindl.aqueous extract is rutin.